The Influence of Customer Relationship Management and Company Reputation on Customer Loyalty Through Customer Satisfaction in Telecommunication Companies - Maria Sugiat; Eky Novrizon; Nurvita Trianasari (International Journal of Economics (IJEC), 2023)
This study aims to examine the influence of customer relationship management (CRM) and company reputation (CR) on customer loyalty (CL) through customer satisfaction (CS) studies at Mitratel companies. The number of samples was 155 respondents from Mitratel’s customers. The approach used in this research is quantitative. The primary data is obtained from the questionnaire and analyzed quantitatively using the SEM PLS technique. The results indicate that CRM and CR affect CS and CL, but the influence of CRM on CL cannot directly influence it. To form high CL, CS must first be improved. The CRM can increase CL if the CRM program can provide CS. There is a significant influence of satisfaction on CL also proves that CS can mediate the influence of CRM and company reputation on CL.